Dielectric dissipation factor in three-core power cables - Kostiukov, Ivan (Видавництво Львівської політехніки, 2021)
This article is devoted to the analysis of components of variance of the results of measurements of dielectric dissipation factor of insulation layers between the conductive elements of the construction of three core power cables with paper impregnated insulation in a common sheath. The analysis of components of variance was carried out by applying presented relations for the direct calculation of the dielectric dissipation factor. The accuracy of presented relations for the calculation of variance components was verified. The results of carried out analysis have shown that the variance of the dielectric dissipation factor measurements is mostly determined by the variances of multiplication of measurements of aggregate values of dielectric dissipation factor and coefficients depending on the partial capacitances of tested three core cable.
Keywords: Testing of insulation; Power cable diagnostics; Insulation deterioration; Aggregate measurements; Electrical capacitance